Impact of Dietary Nitrate on the Recovery of Therapy-related Vascular Health Impairments Following Standard Periodontal Aftercare Therapy: a Hypothesis-generating Subanalysis - Jockel-Schneider, Yvonne; Goßner, Sophia K.; Stölzel, Peggy; Haubitz, Imme; Carle, Reinhold; Petersen, Nicole; Baulmann, Johannes; Schlagenhauf, Ulrich (Planta Medica, 2023)
This follow-up study assessed the impact of a nitrate-rich diet on salivary nitrate/nitrite levels and the recovery of therapy-induced vascular impairments in a cohort of 39 periodontitis patients treated by standard subgingival mechanical plaque removal (PMPR). At baseline, saliva samples for nitrate/nitrite analysis were collected, and peripheral/central blood and augmentation pressure was documented using the Arteriograph recording system. Immediately after, PMPR vascular parameters were reassessed. All study patients received a randomly allocated supply of a lettuce beverage to be consumed for 14 days, containing either a daily dosage of 200 mg nitrate (test group, n = 20) or being void of nitrate (placebo group, n = 19). At day 14, salivary and vascular parameters were reassessed. Initial salivary and vascular parameters did not differ significantly between the groups. PMPR impaired all vascular parameters in both groups with no differences between the groups. At day 14, salivary nitrate/nitrite levels of the test group were significantly elevated compared to baseline. All vascular parameters had significantly recovered from the impairment inflicted by PMPR. In the placebo group, by contrast, salivary parameters did not differ significantly from baseline, and the recovery of impaired vascular parameters was restricted to a significant improvement of diastolic blood pressure. Correlation analysis identified a significant inverse correlation between salivary nitrate/nitrite sum and central/peripheral blood pressure and augmentation pressure. In conclusion, the data of this subanalysis suggest that increasing salivary nitrate/nitrite levels by a diet rich in nitrate may improve recovery of therapy-induced vascular impairments after PMPR.
Keywords: Nitrate; nitrite; saliva; bacteremia; lettuce; vascular; diet